2017
DOI: 10.5812/ijvlms.13860
|View full text |Cite
|
Sign up to set email alerts
|

Presenting a Framework for Effective E-Mentoring Relationships in Medical Sciences: A Meta-Synthesis Method

Abstract: Background: Mentoring is used as a developmental model in many academic disciplines including clinical medicine and public

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…These utterances demonstrate strong relational values and interpersonal connections that significantly influenced their learning experiences during this mentoring journey (Early 2020). Trust between the mentor, the mentee, and the instructional designer as was revealed in their narratives indeed played a crucial role in the success of their ementoring relationship (Salimi, Mohammadi, and Hosseini 2017).…”
Section: Increased Sense Of Worthmentioning
confidence: 90%
See 2 more Smart Citations
“…These utterances demonstrate strong relational values and interpersonal connections that significantly influenced their learning experiences during this mentoring journey (Early 2020). Trust between the mentor, the mentee, and the instructional designer as was revealed in their narratives indeed played a crucial role in the success of their ementoring relationship (Salimi, Mohammadi, and Hosseini 2017).…”
Section: Increased Sense Of Worthmentioning
confidence: 90%
“…E-mentoring is generally less expensive than contact mentoring because of the reduced travelling costs involved (Salimi, Mohammadi, and Hosseini 2017). It does not only bridge geographical distance but also contributes to the acquisition of improved communication, writing, and teamwork skills (Neely, Cotton, and Neely 2017).…”
Section: The "What" "Why" and "How" Of E-mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on some studies (e.g. Karanjam et al , 2017; Akbari et al , 2017; Salimi et al , 2017), the basis for selecting texts is more than 30, and some other studies of less than 30. So in this research, texts that have received less than 30 scores are excluded from further research.…”
Section: Methodsmentioning
confidence: 99%
“…In the information age, the process of globalization has introduced a new paradigm in human learning, and universities increasingly seek to harness the benefits of emerging technologies in their educational activities (Ruggie, University, USA, University, & USA, 2017). Research has shown that using e-learning in medical education has increased in recent decades (Salimi, Mohammadi, & Hosseini, 2017). There are two major uses of information and communication technology in medical education, one is to improve access to educational resources and the other is to enhance collaboration and communication between teachers and learners (Amin, Joo, & Jamali, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%